"Kara” Kelimesinin Dede Korkut Oğuznameleri'ndeki Kullanımı Üzerine - Memiş, Muhammet Raşit; Kara, Mehmet (Muş Alparslan Üniversitesi, 2018)
The Book of Dede Korkut, in terms of Turkish cultural history and philology, is a very important work. Many words were spoken about the language and the importance of this Turkish cultural treasure, many works have been done and it is still going on. Dede Korkut Stories maintains its update as both language and content and contains messages of many national and universal values for today's people. There is a special use and meaning of color names in Turkish language, culture and social life. “Kara” (black) has been the most commonly used word in different meanings since early history.  In this study, an attempt was made to qualitatively and quantitatively determine the word "kara"(black) most frequently used in all periods of Turkic and in the stories of Dede Korkut, and an analysis of the word "kara"(black) was made in terms of work, genre and semantics.

Korkut Kitabı, Türk kültür tarihi ve filolojisi bakımdan son derece önemli bir eserdir. Bu Türk kültür hazinesinin dili ve önemi üzerine pek çok söz söylenmiş, birçok çalışma yapılmış ve hâlâ yapılmaya devam etmektedir. Dede Korkut Hikâyeleri, hem dil hem de içerik olarak hâlâ güncelliğini korumakta ve günümüz insanına yönelik pek çok millî ve evrensel değerlere ait mesajları içermektedir. Türk dilinde, kültüründe ve sosyal hayatında renk adlarının özel bir kullanımı ve anlamı vardır. “Kara” kelimesi geçmişten günümüze dek renk anlamı dışında, farklı anlamlarıyla sıklıkla kullanılagelmiş bir sözcük olmuştur. Bu çalışmada, Türkçenin bütün dönemlerinde ve Dede Korkut hikâyelerinde çok sık kullanılan bu kelime, nitel ve nicel olarak belirlenmeye çalışılmış ve “kara” kelimesinin görev, tür ve anlamsal olarak bir analizi yapılmıştır.
About the Use of word “Kara” in the Book of Dede Korkut
anemon
Keywords: The Book of Dede Korkut; Color; Black; Dede Korkut Oğuznameleri; Kara; Renk